Korelasi Kekuatan Otot Tungkai, Kelincahan Dan Koordinasi Mata-Kaki Terhadap Kecepatan Dribbling Dalam Permainan Futsal Pada Pemain Futsal Inang Fc Tahun 2021 - Nurkadri, Nurkadri; Kholil, Rois (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2021)
This study aims to determine the correlation of leg muscle strength, agility and eye-foot coordination to the dribbling speed of futsal athletes. The number of samples of 10 people was obtained by total sampling technique. The results of the first statistical analysis showed a Significance Test (0.022 < 0.05) which means that leg muscle strength has a strong relationship to dribbling speed (X1 to Y). The results of the second statistical analysis showed a Significance Test (0.024 < 0.05) which means that agility has a strong relationship with dribbling speed (X2 against Y). The results of the third statistical analysis showed a Significance Test (0.017 < 0.05) which means that eye-foot coordination has a strong relationship to dribbling speed (X3 to Y). The results of the fourth statistical analysis show the Significance Test (0.029 < 0.05) which means that leg muscle strength, agility and eye-foot coordination have a significant correlation to dribbling speed (X1, X2, X3 to Y) so it can be concluded that Simultaneously there is a strong correlation between leg muscle strength, agility and eye-foot coordination on the dribbling speed of Inang FC futsal athletes in 2021. This means that the better the leg muscle strength and the better agility and accuracy of eye-foot coordination, the better the dribbling speed in futsal games.